Dental Materials and Bisphenol-A Exposures - Ridhayani Hatta; Mohamad Arif Budiman Putra Pratama; Ãlida Ortega Asencio (Indonesian Dental Association, 2022)
The utility of dental materials to posing oral diseases have impact in the risk of Bisphenol A (BPA) exposure which can be harmful to human organs. BPA used in dentistry is related to the production of polycarbonate plastics and epoxy resins. For instance, composite filling materials and dental sealant are containing BPA that can promote risk to endocrine-disrupting, estrogenic effect, and renal exposure. The current study is reviewing the BPA exposures of dental materials and it impact risk to the systemic health. This systematic review critically evaluates, and the information gathered form several literatures. The source of these articles was Pub Med and Web of Science, search done with the following terms: BPA of dental materials, BPA exposure, BPA and health risks, BPA, and oral health. BPA exposure found in oral mucosa and saliva after the application of BPA-containing dental materials. BPA derivatives used in dental products have not been evaluated for the endocrine disruptor, estrogenicity. BPA exposures can be absorbed through the oral mucosa and may lead to internal exposures the absorption of BPA from the gastrointestinal tract. Manufacturers should be required to report complete information on the chemical composition of dental materials and strict precaution application techniques must be considered by the practitioner.